15. The \( n^{\text {th }} \) term of a geometric series is \( \mathrm{T}_{n}=x(x+1)^{n-1} \). (a) Determine the constant ratio in terms of \( x \) and in simplest form. (b) If \( x=1 \), determine the sum of the first 25 terms of the series. 16. The sequence 12; \( x ; \ldots \) is a convergent geometrie sequence in which the sum to infi is equal to 24 . (a) Determine the value of \( x \). (b) Hence, determine which term of the sequence is equal to \( \frac{3}{128} \).
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
The constant ratio of the geometric series can be found by comparing consecutive terms. The first term is \( \mathrm{T}_1 = x \) and the second term is \( \mathrm{T}_2 = x(x + 1) \). Thus, the common ratio \( r \) is: \[ r = \frac{\mathrm{T}_2}{\mathrm{T}_1} = \frac{x(x + 1)}{x} = x + 1 \] For the sum of the first 25 terms when \( x = 1 \), we substitute into the formula: \[ \mathrm{T}_n = 1(1 + 1)^{n - 1} = 2^{n - 1} \] The sum \( S_n \) of the first \( n \) terms of a geometric series is given by: \[ S_n = a \frac{r^n - 1}{r - 1} \] Using \( a = 1 \) and \( r = 2 \): \[ S_{25} = 1 \cdot \frac{2^{25} - 1}{2 - 1} = 2^{25} - 1 \] Now onto the convergent geometric sequence! The sum to infinity of a geometric sequence is calculated using: \[ S_\infty = \frac{a}{1 - r} \] Given that \( S_\infty = 24 \) and \( a = 12 \), we set it up: \[ 24 = \frac{12}{1 - r} \] This leads to \( 1 - r = \frac{12}{24} = \frac{1}{2} \) and thus \( r = \frac{1}{2} \). Now, using \( a \) and the common ratio \( r \), the second term \( x \) can be found: \[ x = 12 \cdot r = 12 \cdot \frac{1}{2} = 6 \] To find the term that equals \( \frac{3}{128} \), we have: \[ \mathrm{T}_n = 12 \cdot \left(\frac{1}{2}\right)^{n - 1} \] Setting the term equal to \( \frac{3}{128} \): \[ 12 \cdot \left(\frac{1}{2}\right)^{n - 1} = \frac{3}{128} \implies \left(\frac{1}{2}\right)^{n - 1} = \frac{3}{12 \cdot 128} = \frac{1}{512} \implies \frac{1}{2^{n - 1}} = \frac{1}{2^9} \] Thus, \( n - 1 = 9 \) or \( n = 10 \). So the 10th term equals \( \frac{3}{128} \).